Imagens em crise: construtos de ambiguidade em imagens fotográficas no Instagram - Mattos, Rodrigo Brasil de (Universidade do Vale do Rio dos Sinos, 2020)
The present study treats photography as an image in crisis, which, in constant (re)construction, tensions the elements related to its own constitution. Based on the concept of critical image by Georges Didi-Huberman (1998), the image in crisis emerges from photographic works containing multiple meanings within, developing as a deconstructive way of looking at the contemporary photographic image. With our research corpus based on photographs that circulate on Instagram, the way we explore these photographic works starts from three observation axes that reveal the crisis areas of the photographic image from today. The first deals with the image in crisis from the concept of interface photography. This concept is seen as an update of photography’s way of being that reflects on its new constitution in environments which the photographic image should not be thought of by just considering the referent within the photographic frame, but rather articulated to the interactive elements on the interface (responsible for generating other notions of image). The second axis thinks about the crisis of images through the perspective of the photographic device, which considers the way Instagram affects and conditions, in different ways, the current conjuncture of photographic making. The third and last observation axis deals with the image in crisis’ memorial and historical scope. Through concepts such as the web of imaginariness, it provokes reflections on the constitution of these contemporary photographic works from different fragments of a past that is always present when it returns as a constituent part of these photographs. Thus, the image in crisis poses itself as an articulating concept from different perspectives that stresses contemporary photographic image constructs in their constant (de)constructive flow, which aims to aggregate knowledge to the image studies.
Keywords: Instagram; Imagem crítica; Imagem em crise; Fotografia de interface; Teia de imaginário; Instagram; Critical image; Image in crisis; Interface photography; Web of imaginariness; ACCNPQ::Ciências Sociais Aplicadas::Comunicação